Creating, protecting, and using crop biotechnologies worldwide in an era of intellectual property - Pardey, Philip G.; Koo, Bonwoo; Nottenburg, Carol (2004)
Proponents tout the positive incentive-to-innovate effects of intellectual property rights (IPRs), while others maintain that the expanding subject matter and geographical extent of IPRs are stifling crop research, especially research and development (R&D) dealing with developing-country crop concerns. Much of this debate relies on anecdotes and misleading or incomplete evidence on the extent and nature of the IPRs pertaining to crop technologies, including the jurisdictional extent of the property rights and their practice. In this paper we review the evidence on the scope of agricultural R&D worldwide, provide new data on the structure of crop-related IPRs, and summarize trends on the uptake of proprietary bioengineered crops. (p.i)